Onabotulinum Toxin A Intradetrusor Injections in Children with Neurogenic Lower Urinary Tract Dysfunction: Long-Term Histological Effects on the Bladder Wall - Chiara Pellegrino; Valentina Forlini; Federica Lena; Maria Luisa Capitanucci; Francesca Diomedi Camassei; Enrico Castelli; Giovanni Mosiello (Biomedicines, 2023)
Background: In the last twenty-five years, Onabotulinum Toxin A (BTX-A) has gained increasing popularity for neurogenic lower urinary tract dysfunction (NLUTD) treatment. To maintain its efficacy, repeated BTX-A intradetrusor injections are required over time, with unknown effects on the bladder wall in children. The aim of this paper is to report long-term effects on the bladder wall in children treated with BTX-A. Methods: Children with NLUTD not responsive to anticholinergics were treated with BTX-A, according to our protocol, with bladder wall control using endoscopic cold-cup biopsy. Specimens were evaluated considering edema, chronic inflammation, and fibrosis. Results: Of the 230 patients treated from 1997 to 2022, we considered only specimens obtained in patients who had received ≥5 treatments (36 children), considered as the threshold to evaluate clinical effectiveness on long-term treatment with BTX-A. Most of them had congenital NLUTD (25 patients) and detrusor overactivity (27 patients). In all, increased edema and chronic inflammation with reduced fibrosis over time was reported; these data were not statistically significant. No difference was observed between patients with congenital and acquired diseases. Conclusions: Repeated intradetrusor BTX-A injections are not related to significant histological alterations in children, similarly with adults, and repeated injections could be considered safe.